The higher fraction of VO2max during interval training, the greater gains in performance - Odden, I., Nymoen, L., Urianstad, T., Hammarström, D., Mølmen, K. S., & Rønnestad, B. R. (Journal of Science and Cycling, 2023)
The fraction of maximal oxygen consumption (VO2max) achieved during a high-intensity interval training (HIT) session and the time it is sustained = 90% of VO2max have been suggested as good criterions for judging the effectiveness of the HIT session. However, scientific findings supporting this assumption are surprisingly still unavailable. To our knowledge, the present study is the first who continuously has measured participants oxygen consumption (VO2) during every HIT session throughout an entire exercise training intervention. Our finding that higher fractions of VO2max elicited during HIT sessions translates into greater endurance performance improvements covers a great gap in the existing literature of applied exercise physiology.